Characteristics and outcomes of large artery occlusion-related stroke due to intracranial atherostenosis: An experience from a single center in Saudi Arabia - Azra S. Zafar; Rizwana Shahid; Aishah I. Albakr; Danah T Aljaafari; Fahd A. Alkhamis; Erum M Shariff; Majed M. Alabdali; Saima; Alshamrani Nazish; Foziah J.G. Alshamrani; Abdullah S. Alamri; Kawther M. Hadhiah; Abdulla A Alsulaiman; et al. (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Literature on the frequency, response to treatment, and outcomes of acute ischemic stroke (AIS) due to intracranial atherostenosis (ICAS)-related intracranial large artery occlusion (ILAO) from Saudi Arabia is scarce. The aim of this study was to identify the percentage, describe the characteristics, and observe the treatment response in patients with AIS attributed to ICAS-related ILAO. MATERIALS AND METHODS: This cross-sectional study included all adult patients from 2017-2021 who fulfilled the inclusion criteria for the diagnosis of ICAS-related AIS. Patients were dichotomized based on ILAO. Mortality and functional outcomes (FOCs) based on 90 days' dependence level were compared between the two groups. The association between ILAO and other variables was assessed using the Chi-squared test, odds ratios (OR), and 95% confidence interval (CI). RESULTS: ILAO was found in 38.7% of patients with ICAS-related AIS. Men comprised three-fourths of the cohort and were more frequent in the ILAO group. Smoking was associated with increased (P = 0.04) likelihood of ILAO. Patients with ILAO had more severe strokes (P ≤ 0.001) than patients without. Middle cerebral artery was the most common occluded vessel (52%). Functional dependence (P = 0.003, OR = 2.87, CI = 1.42-5.77), malignant transformation (P = 0.001, OR = 8.0, CI = 1.82-35.9), and mortality (P ≤ 0.001, OR = 7.67, CI = 2.40-24.5) were significantly higher among ILAO group. Patients with ILAO with unfavorable FOC were older than those who achieved better FOC (P ≤ 0.001). Thrombolysis (P = 0.02, OR = 2.50, CI = 1.15-5.41) and mechanical thrombectomy (MT) improved FOC in patients with ILAO (P = 0.04, OR = 2.33, CI = 1.10-4.92). CONCLUSION: ILAO is common in patients with ICAS-related AIS. Timely hyperacute stroke treatment can help improve the FOC of otherwise disabling stroke due to ILAO. Raising awareness of the community about stroke is needed, so that a higher number of patients can arrive at hospital within the golden hours. Further data from the region are required to recognize the efficacy of MT in ICAS-related ILAO.